1982
DOI: 10.1530/jrf.0.0640085
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ovulation and LH secretion in the gilt after treatment with ACTH or hydrocortisone

Abstract: Treatment with ACTH (100 i.u.) or hydrocortisone acetate (250 mg) twice daily for 12 days to increase cortisol concentrations blocked ovulation in all gilts. The preovulatory surge of LH was also blocked in the treated gilts. Oestrous cycle length and number of days in oestrus were similar for all treatments except that in one of the 2 experiments ACTH suppressed oestrus in 4 of the 5 gilts treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
1
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 13 publications
7
57
1
1
Order By: Relevance
“…The present study shows that this effect also operates in the female pig and may explain why elevations in plasma cortisol can depress the preovulatory surge of LH in mature gilts (Barb et al, 1982) and why ACTH suppresses the increase in LH in prepubertal gilts after ovariectomy only when the adrenal glands are present (Fonda et al, 1984). Liptrap & Raeside (1983) reported that short-term cortisol infusions enhanced the pituitary responsiveness of mature boars to exogenous GnRH.…”
Section: Resultssupporting
confidence: 53%
“…The present study shows that this effect also operates in the female pig and may explain why elevations in plasma cortisol can depress the preovulatory surge of LH in mature gilts (Barb et al, 1982) and why ACTH suppresses the increase in LH in prepubertal gilts after ovariectomy only when the adrenal glands are present (Fonda et al, 1984). Liptrap & Raeside (1983) reported that short-term cortisol infusions enhanced the pituitary responsiveness of mature boars to exogenous GnRH.…”
Section: Resultssupporting
confidence: 53%
“…At least 1 week after the placement of i.c.v. cannula, and 24 h prior to treatment, all animals were fitted with indwelling jugular catheters (Barb et al 1982). Animals were randomly assigned to one of three groups.…”
Section: Methodsmentioning
confidence: 99%
“…Pigs were fed to appetite daily, at 0800 and 1700 h, a corn-soybean meal ration (14% crude protein) supplemented with vitamins and minerals, according to the National Research Council guidelines (NRC, 1998). At 1 week after the last ICV surgery, and 24 h before treatment, all pigs were fitted with an indwelling jugular vein cannula (Barb et al, 1982). On the day of the EXP, pigs were fed at 0700 h and blood sampling started at 0800 h. Blood samples were collected every 15 min from 5 h before to 4 h after ICV injections of 150 ml 0.9% saline (S; n 5 4), 25 mg (n 5 4) or 75 mg (n 5 4) of recombinant IGF-I (GroPrep, Adelaide, Australia) in 150 ml of S. Serum was harvested and stored at 2208C until assayed for GH and LH by radioimmunoassay (RIA).…”
Section: Experiments (Exp I)mentioning
confidence: 99%